Plasma biomarkers for systemic inflammation in COVID‐19 survivors. Issue 5 (15th August 2022) - Zhao, Juan; Schank, Madison; Wang, Ling; Dang, Xindi; Cao, Dechao; Khanal, Sushant; Nguyen, Lam N.T.; Zhang, Yi; Wu, Xiao Y.; Adkins, James L.; Pelton, Benjamin J.; Zhang, Jinyu; et al.
Abstract: Background: While the majority of COVID‐19 patients fully recover from the infection and become asymptomatic, a significant proportion of COVID‐19 survivors experience a broad spectrum of symptoms lasting weeks to months post‐infection, a phenomenon termed "post‐acute sequelae of COVID‐19 (PASC)." The aim of this study is to determine whether inflammatory proteins are dysregulated and can serve as potential biomarkers for systemic inflammation in COVID‐19 survivors. Methods: We determined the levels of inflammatory proteins in plasma from 22 coronavirus disease 2019 (COVID‐19) long haulers (COV‐LH), 22 COVID‐19 asymptomatic survivors (COV‐AS), and 22 healthy subjects (HS) using an Olink proteomics assay and assessed the results by a beads‐based multiplex immunoassay. Results: Compared to HS, we found that COVID‐19 survivors still exhibited systemic inflammation, as evidenced by significant changes in the levels of multiple inflammatory proteins in plasma from both COV‐LH and COV‐AS. CXCL10 was the only protein that significantly upregulated in COV‐LH compared with COV‐AS and HS. Conclusions: Our results indicate that several inflammatory proteins remain aberrantly dysregulated in COVID‐19 survivors and CXCL10 might serve as a potential biomarker to typify COV‐LH. Further characterization of these signature inflammatory molecules might improve the understanding of the long‐term impacts of COVID‐19 and provide new targets for the diagnosis and treatment of COVID‐19 survivors with PASC.